National Conference: Engineering Smart Farming for the Next Millenium 14-16 March 1999, IDEAL Conference Centre, UPM Serdang, Selangor - Malaysia, Department of Biological and Agricultural Engineering, Universiti Putra Malaysia; Malaysian Society of Agricultural Engineers (Selangor, Malaysia Universiti Putra Malaysia, 1999)
Summary on booklet cover
Title on booklet cover
Keywords: Agriculture -- Conference